DEVELOPMENT OF OPEN-ENDED STUDENT WORKSHEETS BASED ON MATHEMATICAL CREATIVE THINKING SKILLS IN REVIVAL MATERIALS - Gunawan, Gunawan; Maulida, Farah Isti'anatul; Sugihandardji, Chumaedi; Untarti, Reni (International Journal of Multidisciplinary Research and Literature, 2022)
This study aimed to 1) create students' worksheets (LKPD) for mathematics learning based on Open-Ended Problems on students' mathematical creative thinking skills that meet the validity aspect. 2) create students' worksheets (LKPD) for mathematics learning based on Open-Ended Problems on students' mathematical creative thinking skills that meet practical Aspects. 3) create students' worksheets (LKPD) for mathematics learning based on Open-Ended Problems on students' mathematical creative thinking skills that meet the aspect of effectiveness. This research used 4D development, modified into three stages, namely Define, Design, and Develop.  The trial was carried out in MTs.  Wathoniyah Islamiyah Kebarongan with research subjects of 9 students in Grade IXA. The research found that the mathematics learning worksheets that had been developed met the validity aspects as measured by the assessment of the validation results of experts with an average score of 4.1. The practicality of the LKPD was measured based on the observation of the implementation of the LKPD which was shown to be fulfilled in the fully implemented category.  The teacher's response indicated an average score of 4.0 meaning that the mathematics worksheets are practical for learning activities. The effectiveness of the LKPD was shown by the fulfilment of the established effectiveness indicators, namely the average N-Gain normality test, the results of which were carried out through the results of the pretest and posttest. The N-Gain normality test got an average score of 0.5130 which was interpreted as moderate. Thus, the development of mathematics worksheets effectively affects students' creative thinking abilities. It can be concluded that the LKPD developed is valid, practical, and effective